Impacts of Fertilization on Environmental Quality across a Gradient of Olive Grove Management Systems in Alentejo (Portugal) - Rodríguez Sousa, Antonio (2022)
Olive groves are Mediterranean socioecological systems. In Portugal (350,000 hectares of olive groves), a transition is ongoing towards intensification. Such effects may arise from the incremental use of agrochemical fertilizers. The Alentejo region, Portugal, was stratified according to the olive management systems (i.e., extensive groves managed conventionally, integrated or organically, and intensive and highly intensive farms) and erosive states. Agronomic (i.e., fertilizers) and biological (i.e., herbaceous and lepidopteran richness and biodiversity) variables were quantified in 80 plots so we could know how managements affect biodiversity. Intensive and highly intensive farms showed the highest erosion (up to 48 t ha−1 year−1) and the highest concentration of nitrates (11–16 ppm), phosphates (8–15 ppm), and potassium (169–183 mg kg−1), aligned with its lower flora (null) and fauna (0.50–1.75 species). Conventional extensive farms attained an intermediate position, and integrated and organic managements showed the lowest erosion (up to 20 t ha−1 year−1), and the lowest concentration of nitrates (5–6 ppm), phosphates (2–4 ppm), and potassium (92–125 mg kg−1) aligned with its higher flora (14–27 species) and fauna (up to 8 species). Studies aimed at characterizing the multifunctionality of olive groves are essential in Portugal, also considering how soil practices can minimize externalities driven by rapid changes in crop systems.